Influence of Parental Deprivation on Conduct Disorders among Children from Public Primary Schools in Masaba South, Kisii County, Kenya - Michel, Kiarie O.; Anika, Alice A.; Sarah, Mwangi M.; Lambert, Edward; Level, Rene T.; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2025)
Parental absence which is termed parental deprivation associated negatively with the social and mental development and growth of children which has short-term and long-term effects on the mental conditions of children (Mao, 2020) [31]. The current study aimed to determine parental deprivation's influence on conduct disorder among children in public primary schools in Masaba South, Kisii, Kenya. The research employed a correlation and cross-section study design approach, combining qualitative interviews and focus group discussions. A sample of 324 participated in the study. The results were Parental living status significantly influenced anxious or depressed scores among children. Children whose parents lived together exhibited a significant decrease of 4.7 units in anxious/depressed scores (β = -4.7, 95% CI [-5.2, -4.2], p < .001) while Children with separated parents showed a significant increase of 2.9 units in these scores (β = 2.9, 95% CI [2.2, 3.6], p < .001). The study revealed a clear link between parental deprivation and conduct disorders. The study demonstrated the need for comprehensive interventions addressing parental deprivation's material and emotional aspects. Recommendations include strengthening social safety nets, enhancing educational resources, promoting positive parenting practices, and addressing economic inequalities. Future research should explore the long-term effects of parental deprivation, the specific mechanisms of its impact on children, and the cultural factors influencing these dynamics.